Effects of local treatment with and without sensorimotor and balance exercise in individuals with neck pain: Protocol for a randomized controlled trial - Munlika Sremakaew (2018)
© 2018 The Author(s). Background: Impaired cervical joint position sense and balance are associated with neck pain. Specific therapeutic exercise and manual therapy are effective for improving neck pain and functional ability but their effects on joint position sense and balance impairments remain uncertain. Changes in the joint position sense and balance may need to be addressed specifically. The primary objective is to investigate the most effective interventions to improve impaired cervical joint position sense and balance in individuals with neck pain. The secondary objective is to assess the effectiveness of the interventions on pain intensity and disability, pain location, dizziness symptoms, cervical range of motion, gait speed, functional ability, treatment satisfaction and quality of life. Methods: A 2 × 2 factorial, single blind RCT with immediate, short- and long-term follow-ups. One hundred and sixty eight participants with neck pain with impaired joint position sense and balance will be recruited into the trial. Participants will be randomly allocated to one of four intervention groups: i) local neck treatment, ii) local treatment plus tailored sensorimotor exercises, iii) local treatment plus balance exercises, and iv) local treatment plus sensorimotor and balance exercises. Participants receive two treatments for 6 weeks. Primary outcomes are postural sway and cervical joint position error. Secondary outcomes include gait speed, dizziness intensity, neck pain intensity, neck disability, pain extent and location, cervical range of motion, functional ability, perceived benefit, and quality of life. Assessment will be measured at baseline, immediately after treatment and at 3, 6, 12 month-follow ups. Discussion: Neck pain is one of the major causes of disability. Effective treatment must address not only the symptoms but the dysfunctions associated with neck pain. This trial will evaluate the effectiveness of interventions for individuals with neck pain with impaired cervical joint position sense and balance. This trial will impact on clinical practice by providing evidence towards optimal and efficient management. Trial registration: ClinicalTrials.gov (NCT03149302). May 10, 2017.